Singing of divine identities in a liturgical space? John Damascene’s treatise on the Trisagion and his anti-heretical polemics - of Xenophontos, Fr Damaskinos (Olkinuora) (Approaching Religion, 2018)
John Damascene, one of the most productive Greek theologians of the Middle Byzantine era, also composed a treatise on the Trisagion hymn, or how it should be sung correctly and why; a text that has been little discussed in contemporary scholarship. The present paper provides an overview of the work – with special reference to the notion of identity in John’s description of the Trinitarian doctrine. It also examines the treatise especially in the context of anti-heretical polemics. The author argues that John’s approach to the question of the correct way of singing the hymn is gentle: instead of using pejorative language, he even praises the object of his reproach.